POLITICAL ECONOMY OF POPULISM - Jerkov, Aleksandra (Poslovna ekonomija, 2024)
This paper examines the political economy of populism, with a focus on Central and Eastern European (CEE) countries. Following the global financial crisis of 2008, Hungary and Poland developed distinct populist economic programs, which have started to influence other CEE countries, including Serbia. This paper explores the causes of populism, the transformation of post-crisis economic models, and the specific economic policies characterizing populist governments in the region. Through in-depth case studies of Hungary, Poland, and Serbia, the research highlights how these policies are underpinned by economic nationalism, workforce activation, natalism, and sovereignty. Furthermore, the paper investigates the impact of these policies on attracting new foreign investment sources, particularly from authoritarian states in the East.